Strategi Pengembangan Ekonomi Kerakyatan Riau - M Rusli Zainal (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2003)
Comunity based economy has only become a choice in the national economics development. This is caused by the lack of entrepreneurs ability and financial capability to run the community based economics system.